The Level of Livelihood Assets Ownership Among Vulnerability Group in East Coast of Malaysia - Zubir Ibrahim, Ahmad; Hj Hassan, Kalthum; Kamaruddin, Roslina; Anuar, Abd Rahim (European Journal of Sustainable Development, 2018)
This paper aim to analyze the level of livelihood assets ownership among vulnerability group in Kelantan, East Coast of Malaysia. A total of 300 respondents comprising the vulnerability group in the rural area, State of Kelantan has been chosen to achieve this goal. Based on Sustainability Livelihood Analysis, a structured questionnaires has been develop to collect information on the livelihood assets, which consist of human, financial, social, natural and physical assets. This study found that the human asset is the key asset which contributes to the livelihood compared to other assets of the vulneralbility group in Kelantan. This study will benefit the policy makers, which directly involved with the development of rural communities. This study also proposes a number of remedies that need to be addressed in order to improve the sustainability of livelihoods among vulnerability group. Keyword: sustainability, vulneralbility group, livelihood assets